Inovasi Camilan Sehat Sweetpomo Untuk Memperbaiki Asupan Gizi Masyarakat Di Pandemi Covid-19 - Edy Yulianto Putra; Alissya Maidha Fitri; Adeline; Angie; Raisy (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2022)
The arrival of the COVID-19 Pandemic has caused the public to put more emphasis on their health, nutrition, and immunity to defend against contracting the virus. However, existing limitations over certain activities has directly affected financial conditions of the public; therefore, making them more inclined to order food using online services that are more often than not unhealthy. This is apparent in one study about the food consumption of teens during the COVID-19 Pandemic in Surabaya that shows 57% of 100 teens buy and purchase street food as much as three times in one day since the pandemic started. In addition to that, the public has found difficulty in engaging in physical activities outside their homes, hence the combination of the two increases the risk of deteriorating immunity and obesity. From that emerged the idea for the healthy snack business SweetPomo that can be the solution for this very problem. SeetPomo is an organic business idea with attainable price that makes use of sweet potatoes as its main ingredient. The purpose of SweetPomo of this business is to improve nutrition intake and help the public in lessening their unhealthy food consumption. The methods implemented are project execution and qualitative research where acquired data are secondary in nature in the form of articles, e-jounrals, and other publications in various sites. The result of this research depicts the plans and concepts of SweetPomo.